Relationship between Birth Weight and Metabolic Status in Obese Adolescents. (28th August 2013) - Hill, David J.; Prapavessis, Harry; Shoemaker, J. Kevin; Jackman, Michelle; Mahmud, Farid H.; Clarson, Cheril
Abstract : Objective . To examine the relationships between birth weight and body mass index, percent body fat, blood lipids, glycemia, insulin resistance, adipokines, blood pressure, and endothelial function in a cohort of obese adolescents. Design and Methods . Ninety-five subjects aged 10–16 years (mean age 13.5 years) with a body mass index >95th centile (mean [±SEM] 33.0 ± 0.6) were utilized from two prospective studies for obesity prevention prior to any interventions. The mean term birth weight was 3527 ± 64 g (range 1899–4990 g;). Results . Body mass index z -score correlated positively with birth weight (r 2 = 0.05, P = 0.03 ), but not percent body fat. Insulin resistance negatively correlated with birth weight (r 2 = 0.05, P < 0.001 ), as did fasting plasma insulin (r 2 = 0.05, P < 0.001 ); both being significantly greater for subjects of small versus large birth weight (Δ Homeostasis Model Assessment = 2.5 and Δ insulin = 10 pmol/L for birth weight <2.5 kg versus >4.5 kg). Adiponectin, but not leptin, blood pressure z -scores or peripheral arterial tomography values positively correlated with birth weight (r 2 = 0.07, P = 0.008 ). Conclusions . Excess body mass index in obese adolescents was positively related to birth weight. Birth weight was not associated with cardiovascular risk factors but represented a significant determinant of insulin resistance.